2012
DOI: 10.1021/jp212346f
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Active Phosphorus-Doped TiO2 Nanoparticles: An EPR Evidence for the Enhanced Charge Separation

Abstract: Phosphorus-doped TiO2 nanoparticles with visible light activity were prepared by sol–gel method by using Ti(IV) isopropoxide and phosphoric acid as precursors. As prepared samples were calcined at different temperatures, and the obtained samples were characterized by X-ray diffraction, UV–vis spectroscopy, Brunauer–Emmett–Teller (BET) surface area analysis, X-ray photoelectron spectroscopy, scanning emission microscopy, electron paramagnetic resonance (EPR) spectroscopy, the photodegradation of methyleneblue (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 43 publications
3
69
0
1
Order By: Relevance
“…Similar to phosphorusdoped TiO 2 , the P atoms originating from BP can be squeezed and diffused into the ATN lattice, allowing the Ti 4+ sites to be replaced by P species and the BP nanoflakes to be connected with cataclastic ATN via the formation of TiOP bonds (Inset of Figure 3c). [30] The incorporation of the ATN and BP nanoflakes was further confirmed by the lattice fringes of both BP and the ATN in the HRTEM image. Figure 3h illustrates the existence of lattice spacings of 0.335 and 0.262 nm, which correspond to the (021) and (040) With the ATN-BP hybrids used as support, the Pd/ATN-BP catalysts were prepared using K 2 PdCl 4 as the precursor and KBH 4 as the reductant.…”
Section: Resultsmentioning
confidence: 80%
“…Similar to phosphorusdoped TiO 2 , the P atoms originating from BP can be squeezed and diffused into the ATN lattice, allowing the Ti 4+ sites to be replaced by P species and the BP nanoflakes to be connected with cataclastic ATN via the formation of TiOP bonds (Inset of Figure 3c). [30] The incorporation of the ATN and BP nanoflakes was further confirmed by the lattice fringes of both BP and the ATN in the HRTEM image. Figure 3h illustrates the existence of lattice spacings of 0.335 and 0.262 nm, which correspond to the (021) and (040) With the ATN-BP hybrids used as support, the Pd/ATN-BP catalysts were prepared using K 2 PdCl 4 as the precursor and KBH 4 as the reductant.…”
Section: Resultsmentioning
confidence: 80%
“…A series of nonmetal elements including N [5][6][7][8], F [9][10][11], S [12], C [13,14] and P [15,16] have been explored, which show that these nonmetal dopants are able to expand the light absorption edge of TiO 2 to the region of visible light thus to improve the photocatalytic activity of materials. In particular, fluorine and nitrogen doping are intensively used for the modification of TiO 2 materials due to their marked thermal stability and cost-effectiveness [17,10].…”
Section: Introductionmentioning
confidence: 99%
“…From these results decrease in crystallite size was observed due to codoping of cobalt and phosphorus into TiO2 lattice. The variation in the particle size and the phase content demonstrated that P doping decreases the particle size, aggravate the unit cell distortion, retards the phase transformation of anatase to rutile [34] and the reducing atmosphere due to P-doping was more efficient in slowing down the crystal-growth rate in P, Co-codoped TiO2 [35,36]. The comparative results of pure TiO2, single doped, phosphorus and cobalt codoped crystallite size with codoped TiO2 are given in the Table 2.…”
Section: X-ray Diffraction Studies (Xrd)mentioning
confidence: 99%